1990
DOI: 10.1159/000116615
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor Cerebri following Eclampsia

Abstract: Pseudotumor cerebri, or increased intracranial pressure without a mass lesion, has been associated with hormonal activity but the exact causative relation is still obscure. We report a case of a 15-year-old girl who developed pseudotumor cerebri manifested by headache, visual symptoms and extraocular muscle palsies 3 weeks after recovering from eclampsia. Possible associations with eclampsia and postpartum changes in estrogen, progesterone and prolactin are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Greer [19] speculated that IIH in pregnancy was due to a physiologic decrease in serum cortisol with a relative adrenal cortical insufficiency during pregnancy. Koppel et al [18] studied the estrogen, progesterone, prolactin, and cortisone levels and found increases during pregnancy, especially in the last trimester, and they associated this to the temporal distribution of IIH in several series. However, no theory has been accepted as a current hypothesis.…”
Section: Pregnancy and Idiopathic Intracranial Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation
“…Greer [19] speculated that IIH in pregnancy was due to a physiologic decrease in serum cortisol with a relative adrenal cortical insufficiency during pregnancy. Koppel et al [18] studied the estrogen, progesterone, prolactin, and cortisone levels and found increases during pregnancy, especially in the last trimester, and they associated this to the temporal distribution of IIH in several series. However, no theory has been accepted as a current hypothesis.…”
Section: Pregnancy and Idiopathic Intracranial Hypertensionmentioning
confidence: 98%
“…There have been isolated reports of IIH in pregnant patients with hyperemesis gravidarum [17] and also eclampsia [18]. These are rare associations Pathophysiology There is no known mechanism, with the most popular hypothesis being that IIH is a syndrome of reduced CSF absorption.…”
Section: Pregnancy and Idiopathic Intracranial Hypertensionmentioning
confidence: 99%